A Simple and Green Protocol for 2H-Indazolo[2,1-b]phthalazine-triones Using Grinding Method - Xiao-chuan Jia; Jing Li; Yu Ding; Bin Zhang; Na Wang; Yu-hu Wang (Journal of Chemistry)
A robust, facile, and solvent-free route for the three-component synthesis of 2H-indazolo[2,1-b]phthalazine-triones in the presence of a catalytic amount of p-toluene sulfonic acid utilizing grinding has been developed. Short reaction time, simple operation, and high yields are the advantages of this protocol.